2016
DOI: 10.1080/21645515.2016.1259045
|View full text |Cite
|
Sign up to set email alerts
|

Dengue vaccine acceptance and willingness to pay

Abstract: The introduction of new vaccines is accompanied by a variety of challenges. Among these, very important ones concern the questions whether the public is willing to accept and willing to purchase the vaccine. Here we discuss factors associated with these questions in the context of vaccines that are becoming available against dengue virus infection. We reviewed published studies available from PubMed and Embase, conducting a meta-analysis when possible and narrative review when the data did not qualify for meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
3
25
1
4
Order By: Relevance
“…According to Harapan et al, factors such as the socioeconomic level, knowledge, attitude and practice regarding dengue fever, and having personally experienced dengue fever, are associated with a greater willingness to pay for a dengue vaccine [25]. However in our study, respondents who had zika infection did not demonstrate a higher value of the willingness to pay compared with those who never had this flaviviruse.…”
Section: Discussioncontrasting
confidence: 79%
“…According to Harapan et al, factors such as the socioeconomic level, knowledge, attitude and practice regarding dengue fever, and having personally experienced dengue fever, are associated with a greater willingness to pay for a dengue vaccine [25]. However in our study, respondents who had zika infection did not demonstrate a higher value of the willingness to pay compared with those who never had this flaviviruse.…”
Section: Discussioncontrasting
confidence: 79%
“…Because of the unprecedented complexity and varying efficacy, the use of this vaccine is recommended only for populations with dengue seroprevalence rates above 80% or to seropositive individuals after screening test . Several studies also have assessed the feasibility and complexity of dengue vaccination within an Indonesian context . Currently, there are no vaccine recommendations that have been released for travellers from nonendemic to endemic countries such as Indonesia …”
Section: Discussionmentioning
confidence: 99%
“…We reviewed several factors associated with dengue vaccine acceptance. Until now (updated-January 2, 2017), only two studies (11,12) evaluated factors associated with dengue vaccine acceptance. Although there were several factors associated with vaccine acceptance from individual study (attitude towards vaccination, preventive measures against dengue, attitude towards dengue, knowledge on dengue fever, socioeconomic level, and dengue experience), our meta-analysis revealed that only attitude towards vaccination and socioeconomic level had significant associations with dengue vaccine acceptance.…”
Section: Factors Associated With Dengue Vaccine Acceptancementioning
confidence: 99%
“…In vaccination programs, a new vaccine has the potential to bring a variety of problems. The problem of dengue vaccine that is categorized as a new vaccine is whether the public will accept and be willing to purchase the vaccine (11) and willingness to pay (WTP).…”
Section: Introductionmentioning
confidence: 99%